Numerical algorithms for solving problems of multiphase flows in porous media - Èiegis, R.; Iliev, O.; Starikovièius, V.; Steiner, K. (Mathematical Modelling and Analysis, 2006)
In this paper we discuss numerical algorithms for solving the system of nonlinear PDEs, arising in modelling of two‐phase flows in porous media, as well as the proper object oriented implementation of these algorithms. Global pressure model for isothermal two‐phase immiscible flow in porous media is considered in this paper. Finite‐volume method is used for the space discretization of the system of PDEs. Different time stepping discretizations and linearization approaches are discussed. The main concepts of the PDE software tool MfsolverC++ are given. Numerical results for one realistic problem are presented.First Published Online: 14 Oct 2010